Advanced Problem in Mechanics II Proceedings of the XLVIII International Summer School-Conference (3z(BAdvanced Problems in Mechanics(3y(B, 2020, St. Petersburg, Russia /s - Indeitsev, D. A.; Krivtsov, A. M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book focuses on original theories and approaches in the field of mechanics. It reports on both theoretical and applied researches, with a special emphasis on problems and solutions at the interfaces of mechanics and other research areas. The respective chapters highlight cutting-edge works fostering development in fields such as micro- and nanomechanics, material science, physics of solid states, molecular physics, astrophysics, and many others. Special attention has been given to outstanding research conducted by young scientists from all over the world. This book is based on the 48th edition of the international conference (3z(BAdvanced Problems in Mechanics(3y(B, which was held in 2020, in St. Petersburg, Russia, and co-organized by The Peter the Great St. Petersburg Polytechnic University and the Institute for Problems in Mechanical Engineering of the Russian Academy of Sciences, under the patronage of the Russian Academy of Sciences. It provides researchers and graduate students with an extensive overview of the latest research and a source of inspiration for future developments and collaborations in mechanics and related fields.s
On the Issue of Analytical Derivation of Stress State in a Cylindrical Shell with a Circular Hole under Axial Tension -- Acoustoelastic Effect during Plastic Deformation of Anisotropic Metals -- Representative elementary volume via averaged scalar Minkowski functionals.
Keywords: Mechanics, Applied; Solids; Composite materials; Multibody systems; Vibration; Aeroacoustics; Solid Mechanics; Composites; Multibody Systems and Mechanical Vibrations; Aeroacoustics; Mechanics -- Congresses